Gum arabic as natural stabilizing agent in green synthesis of ZnO nanofluids for antibacterial application - Norlin, Pauzi; Norashikin, Mat Zain; Nurul Amira, Ahmad Yusof (Elsevier, 2019)
This work is part of a responsible green approach for the development of nanotechnology. Zinc oxide (ZnO) nanofluids are known as one of the versatile inorganic materials used in health-related applications with effective antibacterial activities. In this study, ZnO nanofluids were synthesized by a precipitating method assisted with microwave heating method. Zinc nitrate had been used as zinc salt, sodium hydroxide as reducing agent and gum arabic as a stabilizing agent. The objective of this study was to investigate the effect of gum arabic concentration on the size, optical properties, and stability of ZnO nanofluids. Nanosizer was used for the measurement of the particles size and the average size of ZnO nanofluids was found to be around 200 to 350 nm compared to unstabilized ZnO nanofluids was 1020 nm. The UV–vis absorption spectra were found in the range of 340 nm. The FTIR spectra showed peaks range from 424 to 475 cm−1which indicated a standard peak of ZnO nanofluids. These ZnO nanofluids relatively stabilized for at least 6 months. The antibacterial activities of ZnO nanofluids were tested against Gram-positive bacterium Staphylococcus aureus and Gram-negative bacterium Escherichia coli. Our results showed that stabilized ZnO nanofluids have better antibacterial properties compared to unstabilized ZnO nanofluids.